Frequent aberrant DNA methylation of CDKN2A locus in capillary hemangioblastomas, pheochromocytomas and gliomas - TVERKUVIENĖ, Justina; LAURINAVIČIENĖ, Aida; DANIŪNAITĖ, Kristina; ŠČĖSNAITĖ, Asta; JARMALAITĖ, Sonata (Acta medica Lituanica, 2011)
Background. Both capillary hemangioblastoma (CHB) and pheochromocytoma (PCC) are rare, usually benign tumours occurring sporadically or as part of familial cancer syndromes. The genetic background of most of the inherited cases is well established, but the molecular causes of sporadic cases remains poorly characterized. To better understand the molecular mechanisms of CHB and PCC pathogenesis, we analysed the genetic and epigenetic alterations of the p16 and p14 genes at the CDKN2A locus. Materials and methods. Aberrant methylation of the p16 and p14 genes was analysed in 16 cases with CHB or PCC by means of methylation-specific PCR. The differential polymerase chain reaction was used to prove the occurrence of the genetic deletion of p16. For comparison, 28 cases of glioma – a highly malignant tumour of the brain – was included into the study. Results. Data of our study show that gene p16 is hypermethylated in 25% of CHBs and in 25% of PCCs, while in gliomas this alteration is more frequent (35%) and predominantly occurs in low-grade tumours (67%). Frequent hypermethylation of the p14 gene was observed in PCCs (50%) and CHBs (37.5%), but was less prevalent in gliomas (26%). When all alterations in the CDKN2A locus were considered, including hypermethylation of p16 and p14, and genetic deletion of p16, 75% of PCC, 62.5% of CHB, and 64% of gliomas had at least one alteration of this locus. Conclusions. Our study adds new data to understanding the involvement of the CDKN2A locus in the pathogenesis of CHB and PCC – two of the most common VHL-related tumours. Furthermore, aberrant methylation in the CDKN2A locus is also frequent in gliomas. Keywords: CDKN2A locus, promoter methylation, glioma, capillary hemangioblastoma, pheochromocytoma